Prognostic Value of C-Reactive Protein-to-Lymphocyte Ratio in Combined Immunotherapy and Chemotherapy for Small Cell Lung Cancer - Sheng S; Wu Z; Zheng H; Zhang H; Zhang Q; Liu Z; Wang S; Li X; Li J; Lv J; Hu Y (Journal of Inflammation Research)
Shuyan Sheng, Zhaozhen Wu, Hua Zheng, Hui Zhang, Quan Zhang, Zan Liu, Shouzheng Wang, Xi Li, Jie Li, Jialin Lv, Ying Hu Department of Medical Oncology, Beijing Chest Hospital, Capital Medical University & Beijing Tuberculosis and Thoracic Tumor Research Institute, Beijing, 101149, People’s Republic of ChinaCorrespondence: Ying Hu, Department of Medical Oncology, Beijing Chest Hospital, Capital Medical University/Beijing Tuberculosis and Thoracic Tumor Research Institute, Beijing, 101149, People’s Republic of China, Email huying@bjxkyy.cnPurpose: Inflammatory indexes are emerging as sensible prognostic factors for small cell lung cancer (SCLC). However, the prognostic value of dynamic C-reactive protein-to-lymphocyte ratio (CLR) in SCLC patients treated with chemoimmunotherapy remains unclear.Patients and Methods: This retrospective study investigated 88 SCLC patients who underwent chemoimmunotherapy between January 1st, 2020 and December 12th 2022. We examined the association between CLR and prognostic outcomes after chemoimmunotherapy. The associations between objective response rate (ORR), progression-free survival (PFS) with changes in blood indicators were also analyzed.Results: Patients with decreased CLR had significantly higher ORR, with odds ratios of 3.91 (P< 0.05) and 3.19 (P< 0.05) in univariate and multivariate logistic regression analyses, respectively. Kaplan-Meier analysis showed that decreased CLR was associated with prolonged PFS (P=0.02). Additionally, a CLR higher than 2.47 after treatment was associated with poor survival in both univariate and multivariate analyses.Conclusion: Dynamic CLR can serve as a potential biomarker for predicting the prognosis of SCLC patients treated with chemoimmunotherapy. Reduction of CLR after chemoimmunotherapy is associated with a significantly higher ORR and improved PFS.Keywords: small cell lung cancer, chemoimmunotherapy, C-reactive protein-to-lymphocyte ratio